Reflecting on my Assumptions and the Realities of Arts-Based Participatory Research in an Integrated Dance Community - Kelsie Acton (Engaged Scholar Journal, 2019)
The arts-based research paradigm prioritizes creativity, relationships and the potential of transformative change (Conrad & Beck, 2016). Arts-based research may be useful in disability communities where people may prefer to communicate artistically or through movement, rather than through spoken word (Eales & Peers, 2016). Participatory action research (PAR) involves researchers working with communities to create research critical of dominant power relations and responsive to the needs of communities (McIntyre, 2008). Both arts-based research and PAR value an axiological approach that is responsive to the community’s needs over a dogmatic procedure, meaning that researchers must be reflexive and responsive to the often unexpected realities of the field. Over four months in 2017, eight dancers/researchers from CRIPSiE (Collaborative Radically Integrated Performers Society in Edmonton), an integrated dance company, came together to investigate how integrated dancers practice elements of timing in rehearsal, through an arts-based, participatory process. In this paper I examine the gap between my assumptions of how research should be conducted and the reality of the field, specifically: the tension between university research ethics and the ethics of the CRIPSiE community, the differences between the value of the rehearsal process and the performance as sites of data collection, and the assumptions I had made about the necessity of a singular research question.